Alternative ingredients for halal cosmetic and personal care products - Hashim, Puziah (Halal Products Research Institute, Universiti Putra Malaysia, 2009)
The cosmetic and personal care products are used and become part of our daily life. Due to the increasing awareness, the Muslim consumers are concerned of the safety, quality, composition and the halalness of the cosmetic and personal care products. They want to know the source of the ingredients used and the way it is processed. With the advancement and innovation in cosmetic technology, there are many cosmetic ingredients available today that are derived from various sources including animal. These animal sources may possess or cause some problems of its form; either it is from the forbidden animals such as pig, dog or from the unslaughtered halal animals such as cattle, sheep or chicken. Therefore, the cosmetic ingredients need to be inspected and tested for permissibility to meet the halal compliance. The non-halal source of the raw materials for the cosmetic and personal care products can be substituted with alternative ingredients. This presentation will discuss the details of these alternative ingredients.